The Predictive Value of Thoracic Computed Tomography on the Mortality of Critically Ill COVID-19 Patients - Elif Bombacı; Kemal Tolga Saraçoğlu; Ömer Aydıner; Fulya Ciyiltepe; Ayten Saraçoğlu; Ebru Dülger İliş; Recep Demirhan (Galenos Yayinevi, 2022)
Objective: Although thoracic computed tomography (T-CT) has high sensitivity in the diagnosis of coronavirus disease-2019 (COVID-19), a specific involvement type or region for COVID- 19 has not yet been identified in images consistent with viral pneumonia. This study determined the relationship between the degree of involvement in T-CT and mortality in patients with COVID- 19. Materials and Methods: One hundred and fifteen COVID-19 patients admitted to our intensive care unit were included in this study. Obtained T-CTs were evaluated according to the T-CT severity scoring system. Patients were divided into two groups as the mortality and the survival group. The two groups were compared in terms of age and gender, the presence and localization of abnormal T-CT findings and total CT score. Results: The total CT score was significantly higher in the mortality group than in the survival group (10.88±5.67 vs 8.53±4.89, p=0.048). Bilateral involvement in the T-CT scan was found to be significantly higher in the mortality group. Conclusion: Total CT scoring has predictive value in determining the survival of patients with a critical COVID-19. Bilateral involvement in the T-CT scans performed in the early period of disease and a total CT score of ≥10 may be indicative of mortality in COVID-19 patients.